2020
DOI: 10.4236/ojml.2020.105030
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Machine Translation: An Evaluation of Online Machine Translation of English into Arabic Texts

Abstract: This study compares the translation outputs of an English into Arabic text using the three machine translators of Google Translate, Microsoft Bing, and Ginger. To carry this evaluation of the machine translation (MT) outputs, an English text and its Arabic counterpart were selected from the UN records. The English source text was segmented into 84 semantic chunks. Depending on the Arabic counterpart model text, each chunk was rated as "correct or incorrect" at the two levels of the translation attributes: fide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Results referred to two types: omission and bad word choice. Ali [34] revealed that three MT systems, namely, Google Translate, Microsoft Bing, and Ginger, performed insufficiently. Google translate came last in terms of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Results referred to two types: omission and bad word choice. Ali [34] revealed that three MT systems, namely, Google Translate, Microsoft Bing, and Ginger, performed insufficiently. Google translate came last in terms of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [65] reported that MB was the best engine, while [26] concluded that Reverso Context has a similar performance to GT. Ref.…”
Section: Data Extraction Synthesis and Analysismentioning
confidence: 99%
“…However, the literature has also shown variation and discrepancies in evaluating Arabic MT engines. For instance, some studies show that GT was the least accurate in terms of intelligibility [65] or in dealing with legal discourse. Ref.…”
Section: Data Extraction Synthesis and Analysismentioning
confidence: 99%
“…Machine Translation (MT) systems have made significant progress over the years, as evidenced by numerous research studies assessing their performance (Al-Jarf, 2023;Hutchins, 2001;Hutchin & Somers, 1992;Okpor, 2014). However, when it comes to translating Arabic everyday expressions, the results remain mixed (Ali, 2020;Almahasees, 2021;Ameur, Mezaine, & Guessoum, 2020;At-tall, 2019;Banimelhem & Amayreh, 2023;Harrat, Meftouh & Smaili, 2019;Zakraoui, Saleh, Al-Maadeed & Alja'am, 2021). Most significantly, At-tall (2019) conducted a thesis comparing the performance of Google Translator and human translators in rendering colloquial Arabic expressions from the late Prime Minister Wasfi At-Tall's speeches into English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These systems employ statistical machine translation techniques and utilize vast amounts of parallel bilingual and multilingual data for training their models (Koehn, 2010;Almahasees, 2021). Despite their widespread use, both GT and BT have faced criticism for their limitations in accurately comprehending the hidden meanings of language, particularly when it comes to translating Arabic idiomatic expressions and complex linguistic structures (Aldawsari, 2023;Ali, 2020;Almahasees, 2021;Ameur, Mezaine, & Guessoum, 2020;At-tall, 2019;Harrat, Meftouh & Smaili, 2019;Zakraoui, Saleh, Al-Maadeed & Alja'am, 2021). For instance, a study conducted by Aldawsari (2023) focused on the translations of two MT systems, Google Translate and SYSTRAN, and concluded that both systems "struggled" in accurately translating complex Arabic linguistic features such as homonyms, heteronyms, and polysemes (p. 27).…”
Section: Machine Translationmentioning
confidence: 99%